Policy framework for contract farming: An alternate to Aarthi system in Pakistan - Rana, Abdul Wajid; Gill, Sitara; Akram, Iqra (International Food Policy Research Institute, 2022)
Global agricultural production is undergoing a remarkable shift due to globalization and market liberalization (Setboonsarng et al., 2008). Food markets are transforming from a ‘non-programmed to programmed’ regime stemming from overwhelming changes in demand patterns happening concurrently with variations in production dynamics internationally (Oostendorp, 2018). This presents both the challenge and opportunity to change and adapt to this more structured world to reap benefits for both smallholder farmers and exporters (Setboonsarng et al., 2008).